Ultrasound Evaluation of Internal Jugular Venous Insufficiency and Its Association with Cognitive Decline - Jiu-Haw Yin; Nai-Fang Chi; Wen-Yung Sheng; Pei-Ning Wang; Yueh-Feng Sung; Giia-Sheun Peng; Han-Hwa Hu (Diagnostics)
Background: Prior studies have shown an association between jugular venous reflux and age-related neurological conditions, including cognitive decline and potentially incident dementia. However, a relationship between internal jugular vein (IJV) outflow disturbance and cognitive impairment has yet to be elucidated. This study evaluates the relationship between impaired IJV drainage and cognitive function. Methods: We recruited a prospective sample of 106 participants with subjective memory complaints. Subjects underwent neuropsychological assessments and ultrasound examination of IJV, including time-averaged mean velocity (TAMV) and the cross-sectional area of the IJV at the middle (J2) and distal (J3) segments. Impaired IJV drainage was defined by either of the following: (1) TAMV < 4 cm/s at the J2 or J3 segment on either side, or (2) IJV lumen collapse during inspiration at the J2 segment on either side. Results: The impaired cognition group had a significantly higher prevalence of both impaired flow velocity and impaired IJV drainage compared to the normal cognition group (34% vs. 16%, p = 0.032; 68% vs. 30%, p < 0.001). Furthermore, the impaired IJV drainage group demonstrated lower scores across all neuropsychological tests, with statistical significance observed in the Mini-Mental State Examination (median (IQR) 27 vs. 29, p = 0.013), Montreal Cognitive Assessment (median (IQR) 23 vs. 26, p < 0.001) and Chinese Version of the Verbal Learning Test (median (IQR) 23.5 vs. 27, p = 0.024). Notably, incorporating IJV lumen collapse during deep inspiration into the definition of impaired IJV drainage further increased its prevalence in the impaired cognition group. Conclusions: Our results revealed that the impaired cognition group exhibited a higher prevalence of impaired outflow in the bilateral IJV, while the impaired IJV drainage group scored lower on all neuropsychological tests compared to the normal group. These findings support the hypothesis that impaired IJV drainage is correlated with global cognitive decline.